2022
DOI: 10.1136/bmjopen-2022-063513
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression and its associated factors among women of Godawari Municipality, Lalitpur, Nepal: a cross-sectional study

Abstract: ObjectivesTo estimate the prevalence of antenatal depression and identify its associated factors among pregnant women of Godawari Municipality, Lalitpur, Nepal.DesignCommunity-based cross-sectional study.SettingGodawari Municipality, Lalitpur, Nepal, between September and November 2021.Participants250 randomly selected pregnant women of Godawari Municipality, Lalitpur, Nepal.Main outcome measuresThe level of antenatal depression was assessed using Edinburgh Postnatal Depression Scale. χ2test and multivariate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The majority of studies included in this review were conducted in East Asia and Pacific Area Countries, and in the Middle East. Consistently with the recent literature (Chalise et al, 2022; Prom et al, 2022; Simkhada & van Teijlingen, 2018), our results highlight an imbalance in the geographical distribution of research outputs. The identified gap may help to orient the research agenda for the next years, in order to prioritize critical geographical areas that are still neglected.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of studies included in this review were conducted in East Asia and Pacific Area Countries, and in the Middle East. Consistently with the recent literature (Chalise et al, 2022; Prom et al, 2022; Simkhada & van Teijlingen, 2018), our results highlight an imbalance in the geographical distribution of research outputs. The identified gap may help to orient the research agenda for the next years, in order to prioritize critical geographical areas that are still neglected.…”
Section: Discussionsupporting
confidence: 92%
“…Maternal age [34][35][36] Body Mass Index [37][38][39] Marital status [40,41] Socioeconomic status, maternal leave, partner maternal leave [35,[41][42][43][44][45][46][47][48] Level of physical activity during pregnancy and postpartum [49,50] Smoking status, alcohol consumption, recreational drug use [35,51,52] Personal and family medical history (incl. Current partner abuse [25,43,48,53,[62][63][64]82] Antenatal depression [41,53] -Symptoms of stress and anxiety [43,55,56] Stressful life events [42,55,62] -COVID-19 stress and psychological impact of pandemic [20,83] Sleep quality [84,85] Social media use [86,87] Feeding plans and outcome [88,89] Contraception [80,...…”
Section: Social Support Osss-3mentioning
confidence: 99%
“…In developed countries, a meta-analysis study found that the prevalence rates of depression were 7.4% (2.2–12.6%), 12.8% (10.7–14.8%), and 12.0% (7.4–16.7%) during the first, second, and third trimesters, respectively ( 10 ). A high prevalence of depressive symptoms or probable depression during pregnancy has been reported from developing countries, i.e., 18% in Bangladesh ( 29 ), 24.8% in Nepal ( 30 ), 25 % in Pakistan ( 22 ), 20.2 % in Brazil ( 19 ), 39 % in South Africa Cape Town ( 20 ), 38.5 % in South Africa KwaZulu-Natal ( 21 ), 31% in Limpopo Province South Africa ( 31 ), 39.5 % in Tanzania ( 28 ), 26.9% in Ghana ( 32 ), 29.4% in Nigeria ( 33 ), and 15.2 %−35.4% in Ethiopia ( 9 , 34 36 ).…”
Section: Introductionmentioning
confidence: 99%